Seawater electrolysis hydrogen production catalyst capable of dynamically repelling chloride ions as well as preparation method and application of seawater electrolysis hydrogen production catalyst
By constructing a core-shell nanostructure that dynamically repels chloride ions on the surface of the catalyst, and using the negative charge properties of GQDs to repel chloride ions, the catalyst corrosion problem caused by chloride ions in seawater is solved, and the catalyst's high stability and activity in electrolytic seawater is achieved.
Patent Information
- Application Number
- CN202411881119.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-11
AI Technical Summary
The presence of a large number of chloride ions in seawater causes the anode chlorine oxidation reaction to compete with the redox reaction, which reduces the Faraday efficiency and accelerates the corrosion of the catalyst. The existing catalysts cannot be effectively used to electrolyze seawater.
By constructing a core-shell nanostructure that dynamically repels chloride ions on the surface of the catalyst, the negative charge properties of GQDs repel chloride ions, preventing their adsorption and accumulation, thereby protecting catalytically active sites.
The high stability and activity of the catalyst in alkaline seawater has been achieved, which significantly inhibits the formation of chlorine and hypochlorite, and extends the service life of the catalyst.
Smart Images

Figure CN119593006A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic materials, and in particular to a catalyst for electrolyzing seawater to produce hydrogen with the ability to dynamically exclude chloride ions, and a preparation method and application thereof. Background Art
[0002] Driven by the dual needs of global energy transformation and environmental protection, it is imperative to explore and develop a modern new energy system. Green hydrogen produced by water electrolysis technology driven by renewable energy sources such as solar energy and wind energy is a zero-carbon emission, high-energy-density and renewable energy. However, the current water electrolysis electrolyzer technology requires ultrapure deionized water with a resistivity of 18.2MΩcm, which will increase the cost of hydrogen production and aggravate the freshwater resource crisis. Seawater resources are abundant, and seawater electrolysis can make full use of renewable energy sources such as offshore wind and solar energy, which is a very promising hydrogen production strategy. However, there are a large number of chloride ions in seawater, which are prone to two-electron transfer at the anode and compete with OER, resulting in low Faraday efficiency. In addition, the generated chlorine or hypochlorite will accelerate the corrosion of the catalyst and adversely affect the stability of the electrolyzer, which makes most of the previously developed catalysts unusable for seawater electrolysis. Therefore, it is very necessary to develop high-performance and corrosion-resistant OER catalysts.
[0003] Construct a barrier layer on the catalyst surface to prevent Cl - Adsorption or construction of a repellent layer on the catalytic active site to reduce the Cl - The concentration of 20% is an effective way to improve the corrosion resistance of catalysts. However, the construction of traditional barrier layers and avoidance layers usually coats the entire catalyst surface, which is not only difficult to prepare, but also has some impact on the exposure of the active sites of the catalyst. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a catalyst for hydrogen production by electrolysis of seawater with dynamic exclusion of chloride ions, a preparation method thereof, and its application in oxygen evolution in seawater. The catalyst not only exhibits extraordinary stability and activity in an alkaline seawater electrolysis environment, but also can dynamically exclude Cl - The effect effectively prevented Cl - The adsorption and accumulation on the catalyst surface slows down the corrosion of the catalyst by chloride ions and protects the catalytic active sites from damage.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is a method for preparing a catalyst for electrolyzing seawater to produce hydrogen with dynamic exclusion of chloride ions, comprising the following steps:
[0007] Selenium powder, hydrazine hydrate, thiourea, ammonium fluoride, mixed solvent, molybdenum source and sodium borohydride are mixed evenly and dissolved completely to obtain reaction solution I;
[0008] Adding nickel foam into the reaction solution I to carry out a solvothermal reaction I;
[0009] After the solvothermal reaction I is completed, GQDs dispersion and water are added to the reaction system to carry out the solvothermal reaction II to obtain the seawater electrolysis hydrogen production catalyst.
[0010] The principle of the present invention is as follows:
[0011] In the first step of the hydrothermal reaction, thiourea as a sulfur source decomposes to produce H2S gas. H2S then reacts with the nickel foam substrate to initially form NiS nanoparticles as growth seeds. Subsequently, selenium ions (Se 2- ) was introduced into the reaction system, and the transformation from NiS to NiS / Se nanorods was achieved by replacing some sulfur atoms in NiS. In this process, part of the Ni element dissolved in the solution, providing Ni for the subsequent Mo doping. 2+ ion source, which promotes the continuity of the reaction and the formation of the composite structure. Then, under the combined action of the strong reducing agent hydrazine hydrate and NaBH4, amorphous Mo was successfully doped onto the surface of NiS / Se nanorods to form Mo–NiS / Se@GQDs nanosheets. This process not only enriches the composition of the catalyst, but also further increases the complexity and surface area of the catalyst through the growth of nanosheets, providing an ideal platform for the subsequent anchoring of GQDs. In the second step of the hydrothermal reaction, GQDs, as the key functionalization element, are uniformly anchored on the surface of Mo–NiS / Se@GQDs nanosheets, completing the construction of the core-shell nanostructure. This step not only utilizes the negative charge properties of GQDs to repel chloride ions, but also further improves the overall performance of the catalyst through its unique physicochemical properties.
[0012] The second technical solution of the present invention is a catalyst for hydrogen production by electrolysis of seawater with dynamic exclusion of chloride ions prepared by the above method.
[0013] A third technical solution of the present invention is the use of the above-mentioned seawater electrolysis hydrogen production catalyst with dynamic chloride ion rejection in seawater electrolysis oxygen evolution.
[0014] The present invention discloses the following technical effects:
[0015] The present invention successfully synthesized the Mo-NiS / Se@GQDs core-shell nanorod catalyst with surface-anchored GQDs on nickel foam (NF) by a two-step hydrothermal method, and the preparation method is simple.
[0016] The surface-anchored GQDs Mo-NiS / Se@GQDs catalyst synthesized by the present invention (hydrogen production catalyst by electrolysis of seawater with dynamic exclusion of chloride ions) was tested for its OER performance in 1M KOH alkaline seawater using a three-electrode system. The results showed that the catalyst only required an overpotential of 160-200mV to reach 10mA cm -2 The current density is much higher than that of RuO2 (322 mA cm -2 The catalyst was tested by chronopotentiometry at 100 mA cm -2 The OER stability under the condition of 100-200 hours of continuous reaction, the activity of the catalyst did not decrease significantly. The root of this extraordinary catalytic stability is that GQDs dynamically and effectively repel chloride ions on the catalytic interface, thereby significantly inhibiting the formation of chlorine and hypochlorite. In summary, Mo-NiS / Se@GQDs catalyst has great application potential in the field of hydrogen production by electrolysis of seawater due to its excellent OER activity, efficient charge transfer ability and excellent stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 Schematic diagram of the synthesis of Mo-NiS / Se@GQDs catalyst in the present invention.
[0019] Figure 2 This is the scanning electron microscope (SEM) image of the Mo-NiS / Se@GQDs catalyst in Example 1.
[0020] Figure 3 This is the transmission electron microscopy (TEM) image of the Mo–NiS / Se@GQDs catalyst in Example 1.
[0021] Figure 4 This is the scanning transmission electron microscopy-energy dispersive x-ray spectroscopy (STEM-EDS) image of the Mo-NiS / Se@GQDs catalyst in Example 1.
[0022] Figure 5 This is the spherical aberration corrected transmission electron microscopy scanning electron microscopy (HAADF-STEM) image of the Mo–NiS / Se@GQDs catalyst in Example 1.
[0023] Figure 6X-ray powder diffraction (XRD) patterns of the Mo–NiS / Se@GQDs catalyst of Example 1 and the Mo–NiS / Se catalyst of Comparative Example 1.
[0024] Figure 7 This is a comparison chart of the linear sweep voltammetry (LSV) test of OER in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3.
[0025] Figure 8 This is a comparison chart of the OER stability tests of the Mo–NiS / Se@GQDs catalyst of Example 1 and the Mo–NiS / Se catalyst of Comparative Example 1.
[0026] Fig. 9 The C and Cl of the Mo-NiS / Se@GQDs catalyst of Example 1 and the Mo-NiS / Se catalyst of Comparative Example 1 after 2000 CV cycles - OH - Time-of-flight secondary ion mass spectrometry (TOF-SIMS) depth profile of species.
[0027] Fig.10 The potential kinetic polarization curves of the Mo-NiS / Se@GQDs catalyst of Example 1 and the Mo-NiS / Se catalyst of Comparative Example 1 in alkaline seawater.
[0028] Fig.11 Schematic diagram of the dynamic exclusion of chloride ions by the anode of the seawater electrolysis hydrogen production catalyst (i.e., Mo-NiS / Se@GQDs catalyst) in the present invention. DETAILED DESCRIPTION
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] Graphene quantum dots (GQDs), as an emerging graphene material, have abundant active sites and exhibit negative charge properties. Therefore, it is potential to construct space charge repulsion catalyst surface Cl- adsorption by GQDs.
[0035] The first aspect of the present invention provides a method for preparing a catalyst for electrolyzing seawater to produce hydrogen with a dynamic chloride ion rejection, characterized in that the method comprises the following steps:
[0036] Selenium powder, hydrazine hydrate, thiourea, ammonium fluoride, mixed solvent, molybdenum source and sodium borohydride are mixed evenly and dissolved completely to obtain reaction solution I;
[0037] Adding nickel foam into the reaction solution I to carry out a solvothermal reaction I;
[0038] After the solvothermal reaction I is completed, GQDs dispersion and water are added to the reaction system to carry out the solvothermal reaction II to obtain the seawater electrolysis hydrogen production catalyst.
[0039] In some embodiments of the present invention, the selenium powder, hydrazine hydrate, thiourea, ammonium fluoride, a mixed solvent, a molybdenum source and sodium borohydride are mixed evenly, and after they are completely dissolved, a reaction solution I is obtained. Specifically, the selenium powder is first dissolved in hydrazine hydrate, and then thiourea, ammonium fluoride and a mixed solvent are added and dissolved, and then a molybdenum source is added. After the molybdenum source is dissolved, sodium borohydride is added, and after the sodium borohydride is dissolved, the reaction solution I is obtained.
[0040] The present invention does not impose any particular limitation on the specific method of dissolution, and any technical means well known to those skilled in the art may be used, such as stirring to dissolve.
[0041] In some embodiments of the present invention, the mixed solvent is a mixed solution of ethanol and water in a volume ratio of 1:1; the molybdenum source is molybdenum oxide; the mass volume ratio of the selenium powder, hydrazine hydrate, thiourea, ammonium fluoride, mixed solvent, molybdenum oxide and sodium borohydride is 0.2-0.3g: 5-15mL: 0.2~0.3g: 0.5~0.7g: 10-30mL: 0.1-0.2g: 1-2mg.
[0042] In some embodiments of the present invention, before adding the nickel foam to the reaction solution I for the solvothermal reaction I, the step of pretreating the nickel foam is also included; the pretreatment is specifically: immersing the nickel foam (NF) in a hydrochloric acid solution for ultrasonic treatment, then washing with deionized water, acetone and ethanol in sequence to remove oxides on the surface of the NF, and finally drying; the concentration of the hydrochloric acid is preferably 1-3M, the time of the ultrasonic treatment is preferably 5-20min, and the drying is: vacuum drying at 50-70°C for 5-7h.
[0043] In some embodiments of the present invention, the temperature of the solvent thermal reaction I is 150-220° C. and the time is 10-25 hours.
[0044] In some embodiments of the present invention, the concentration of the GQDs dispersion is 1 mg ml -1 ; The mass volume ratio of the selenium powder, GQDs dispersion and water is 0.2-0.3g:0.5-2mL:10-20mL.
[0045] In some embodiments of the present invention, the reaction temperature of the solvothermal reaction II is 100-150° C. and the reaction time is 2-5 hours.
[0046] In some embodiments of the present invention, after the solvothermal reaction II is completed, the steps of washing and drying the obtained product are also included; the washing is washing with deionized water for 3 to 5 times; the drying is freeze-drying for 36 to 48 hours.
[0047] A second aspect of the present invention provides a catalyst for producing hydrogen by electrolyzing seawater that dynamically repels chloride ions and is prepared by the above-mentioned preparation method.
[0048] A third aspect of the present invention provides an application of the above-mentioned seawater electrolysis hydrogen production catalyst with dynamic chloride ion rejection in seawater electrolysis oxygen evolution.
[0049] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0050] In order to better understand the present invention, the content of the present invention is further explained in conjunction with the following examples, but the content of the present invention is not limited to the following examples. The synthesis schematic diagram of the electrolytic seawater hydrogen production catalyst for dynamic chloride ion rejection of the present invention is as follows Figure 1 shown.
[0051] In the embodiment, the nickel foam (NF) used is pretreated NF, and the pretreatment is specifically: the NF is cut into a size of 1 cm×2.5 cm and then immersed in a 3M hydrochloric acid solution for ultrasonication for 10 minutes, and then washed with deionized water, acetone and ethanol in turn to remove the oxide on the surface of the NF, and the treated NF is dried in a vacuum drying oven at 60°C for 6 hours.
[0052] Example 1
[0053] This embodiment provides a catalyst for hydrogen production by electrolysis of seawater that dynamically repels chloride ions, and the preparation method is as follows:
[0054] (1) Dissolve 0.32g of selenium powder in 15mL of hydrazine hydrate and stir for 20min; then add 0.31g of thiourea, 0.65g of ammonium fluoride, 15mL of ethanol and 15mL of water, stir for 20min, add 0.18g of molybdenum oxide, stir for another 20min, add 0.003g of sodium borohydride to the solution, and stir slowly for 10min. Add the obtained solution and the pretreated NF into a 100ml polytetrafluoroethylene-lined stainless steel autoclave and perform a solvothermal reaction at 200℃ for 24h.
[0055] (2) Add 2 mL of GQDs dispersion (concentration 1 mg ml) to the cooled solution after the solvothermal reaction. -1 ) and 18 mL of deionized water, and the reaction was continued at 150 ° C for 3 hours. After the solvothermal treatment, the autoclave was cooled with water, the obtained product was washed three times with deionized water, and then freeze-dried for 48 hours to obtain a hydrogen production catalyst for electrolysis of seawater with dynamic exclusion of chloride ions (denoted as Mo-NiS / Se@GQDs). The dried sample was stored in a vacuum drying oven to prevent oxidation.
[0056] Depend on Figure 2 It can be seen that the catalyst synthesized in Example 1 is a neat array of nanorods. Transmission electron microscope (TEM) image ( Figure 3 ) confirmed that the nanosheets were successfully coated on the nanorods to form a clear core-shell structure, verifying our synthesis strategy and design ideas. Figure 4 It can be seen that Mo was successfully introduced into the material and Ni, S and Se were uniformly distributed throughout the sample. In addition, spherical aberration corrected transmission electron microscopy (HAADF-STEM) revealed the distribution of GQDs, such as Figure 5As shown. This shows that GQDs were successfully introduced into the nanosheet structure of the sample. Figure 6 It can be seen that the Mo–NiS / Se@GQDs catalyst has two phases of NiS and NiSe, indicating the formation of a heterojunction.
[0057] Comparative Example 1
[0058] 0.32 g of selenium powder was dissolved in 15 mL of hydrazine hydrate and stirred for 20 min. Then 0.31 g of thiourea, 0.65 g of ammonium fluoride, 15 mL of ethanol and 15 mL of water were added. After stirring for 20 min, 0.18 g of molybdenum oxide was added. After stirring for another 20 min, 0.003 g of sodium borohydride was added to the solution and stirred slowly for 10 min. The obtained solution and the pretreated NF were placed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave and subjected to solvothermal reaction at 200 ° C for 24 h. After solvothermal treatment, the autoclave was cooled with water, and the obtained Mo–NiS / Se was washed three times with deionized water and then freeze-dried for 48 h. The dried sample was stored in a vacuum drying oven to prevent oxidation. The catalyst prepared in this comparative example is recorded as Mo–NiS / Se@ (that is, compared with Example 1, the addition of GQDs is omitted).
[0059] Comparative Example 2
[0060] In this comparative example, RuO2 catalyst is prepared by dropping RuO2 ink onto nickel foam, and the specific preparation method is as follows:
[0061] (1) 0.1 ml of deionized water, 0.4 ml of isopropanol and 20 mg of Nafion solution (5%) were mixed, and then 4 mg of RuO2 powder was added. After mixing, ultrasonic treatment was performed for 40 minutes to obtain a uniform mixed ink.
[0062] (2) 50 μl of the mixed ink was evenly dripped onto the front and back surfaces of the pretreated NF four times, and then the nickel foam was placed in a vacuum drying oven and vacuum dried at 70°C for 5 h to obtain a RuO2 catalyst.
[0063] Comparative Example 3
[0064] In this comparative example, the pretreated nickel foam is directly used as an OER catalyst.
[0065] The catalysts obtained in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were used in the oxygen evolution reaction (OER) performance test results of alkaline seawater are as follows:
[0066] Depend on Figure 7 The linear sweep voltammetry (LSV) curve shows that when the current reaches 10 mA cm -2At a current density of 100 mA cm, Mo–NiS / Se@GQDs only requires an overpotential of 170 mV, which is slightly better than unmodified Mo–NiS / Se (172 mV) and significantly better than traditional noble metal catalysts RuO2 (322 mV) and nickel foam (717 mV). Furthermore, at a higher current density (100 mA cm -2 and 300mAcm -2 ), Mo–NiS / Se@GQDs also showed superior performance, requiring overpotentials of 306mV and 395mV, respectively, which are significantly better than Mo–NiS / Se (325mV and 415mV) and RuO2 (488mV and 698mV). These results show that the introduction of GQDs significantly improves the OER activity of Mo–NiS / Se catalysts.
[0067] Figure 8 The stability test results show that the activity of Mo–NiS / Se@GQDs did not decrease significantly after 100 hours of continuous reaction, while the catalytic activity of Mo–NiS / Se decreased significantly after about 4 hours. Moreover, Mo–NiS / Se@GQDs showed no significant decrease in the catalytic activity after 100 hours of continuous operation and high current density (400mAcm -2 ) can maintain excellent catalytic activity under the conditions of high temperature and low pressure. This proves its high stability and corrosion resistance in seawater hydrogen production applications.
[0068] The catalysts of Example 1 and Comparative Example 1 were further characterized for corrosion resistance, demonstrating their ability to dynamically inhibit chlorine corrosion in the alkaline seawater OER reaction:
[0069] First, depth profiling experiments were performed on the catalysts by time-of-flight secondary ion mass spectrometry (TOF-SIMS) to evaluate the Cl - The distribution depth of ions in the catalyst. Fig. 9 As shown in Figure 2, after 2000 OER cycles, the Cl - The distribution depth of ions is significantly lower than that of Mo–NiS / Se, which directly proves that GQDs can effectively resist Cl - The ions have a significant repulsive effect, effectively preventing them from corroding the catalyst surface. In addition, TOF-SIMS data also revealed that C and OH in Mo-NiS / Se@GQDs - The content of GQDs increased significantly compared with that of unmodified Mo–NiS / Se catalyst. This finding not only confirms the successful introduction of GQDs, but also shows that GQDs have an attractive effect on OH- ions, which may play a positive role in proton transfer and intermediate stabilization during the OER reaction. Potentiodynamic polarization curve ( Fig.10) further demonstrated the advantages of Mo–NiS / Se@GQDs in corrosion resistance. Its corrosion potential (0.66 V) was higher than that of Mo–NiS / Se (0.609 V), and its corrosion current density (122.93 μA cm -2 ) is lower (180.29μAcm -2 ). These results are consistent with the general rule that high corrosion potential and low corrosion current density indicate stronger corrosion resistance, which strongly proves the important role of GQDs in improving the corrosion resistance of Mo–NiS / Se catalysts.
[0070] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a catalyst for hydrogen production by electrolysis of seawater with dynamic exclusion of chloride ions, characterized in that: The following steps are involved: Selenium powder, hydrazine hydrate, thiourea, ammonium fluoride, mixed solvent, molybdenum source and sodium borohydride are mixed evenly and dissolved completely to obtain reaction solution I; Adding nickel foam into the reaction solution I to carry out a solvothermal reaction I; After the solvothermal reaction I is completed, GQDs dispersion and water are added to the reaction system to carry out the solvothermal reaction II to obtain the seawater electrolysis hydrogen production catalyst.
2. The method for preparing a catalyst for hydrogen production by electrolysis of seawater with dynamic chloride ion rejection according to claim 1, characterized in that: The selenium powder, hydrazine hydrate, thiourea, ammonium fluoride, a mixed solvent, a molybdenum source and sodium borohydride are mixed evenly, and after the dissolution is completed, a reaction solution I is obtained. Specifically, the selenium powder is first dissolved in hydrazine hydrate, and then thiourea, ammonium fluoride and a mixed solvent are added and dissolved, and then the molybdenum source is added, and after the molybdenum source is dissolved, sodium borohydride is added, and after the sodium borohydride is dissolved, the reaction solution I is obtained.
3. The method for preparing a catalyst for hydrogen production by electrolysis of seawater with dynamic chloride ion rejection according to claim 1, characterized in that: The mixed solvent is a mixed solution of ethanol and water in a volume ratio of 1:1; the molybdenum source is molybdenum oxide; the mass volume ratio of the selenium powder, hydrazine hydrate, thiourea, ammonium fluoride, mixed solvent, molybdenum oxide and sodium borohydride is 0.2-0.3g: 5-15mL: 0.2~0.3g: 0.5~0.7g: 10-30mL: 0.1-0.2g: 1-2mg.
4. The method for preparing a catalyst for hydrogen production by electrolysis of seawater with dynamic chloride ion rejection according to claim 1, characterized in that: The temperature of the solvent thermal reaction I is 150-220° C. and the time is 10-25 hours.
5. The method for preparing a catalyst for hydrogen production by electrolysis of seawater with dynamic chloride ion rejection according to claim 1, characterized in that: The concentration of the GQDs dispersion was 1 mg ml -1 ; The mass volume ratio of the selenium powder, GQDs dispersion and water is 0.2-0.3g:0.5-2mL:10-20mL.
6. The method for preparing a catalyst for hydrogen production by electrolysis of seawater with dynamic chloride ion rejection according to claim 1, characterized in that: The reaction temperature of the solvent thermal reaction II is 100-150° C. and the reaction time is 2-5 hours.
7. The method for preparing a catalyst for hydrogen production by electrolysis of seawater with dynamic chloride ion rejection according to claim 1, characterized in that: After the solvent thermal reaction II is completed, the steps of washing and drying the obtained product are also included.
8. A catalyst for hydrogen production by electrolysis of seawater with dynamic chloride ion rejection, prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the catalyst for hydrogen production by electrolysis of seawater with dynamic chloride ion rejection as claimed in claim 8 in oxygen evolution by electrolysis of seawater.